2011
DOI: 10.1109/tc.2010.167
|View full text |Cite
|
Sign up to set email alerts
|

Pipelined Statistical Cipher Feedback: A New Mode for High-Speed Self-Synchronizing Stream Encryption

Abstract: -In this paper, we introduce a new block cipher mode of operation targeted to providing high speed hardware-based self-synchronizing stream encryption. The proposed mode is a modification of statistical cipher feedback (SCFB) mode and is designed to be implemented using pipeline architectures for the block cipher. We refer to the mode as pipelined SCFB mode or PSCFB. In this paper, we consider the implementation characteristics and show that PSCFB is able to achieve speeds that are very close to pipelined bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 9 publications
(36 reference statements)
0
32
0
Order By: Relevance
“…It provides automatic resynchronization by modifying block cipher as a stream cipher, which is self-synchronizing (Heys and Zhang, 2011).…”
Section: Cipher Feedback Modementioning
confidence: 99%
“…It provides automatic resynchronization by modifying block cipher as a stream cipher, which is self-synchronizing (Heys and Zhang, 2011).…”
Section: Cipher Feedback Modementioning
confidence: 99%
“…Based on the proposed structure in [2] and illustrated in Fig. 3, a plaintext queue and ciphertext queue are two significant parts which can affect the speed of the PSCFB system.…”
Section: Plaintext Queue In Encryptionmentioning
confidence: 99%
“…The minimum size of plaintext and ciphertext queue is M = B + 3D − 2 = 444, with B = 128 and input rate D = 116 [2]. This provides the maximum efficiency of D/B = 90.625% without any overflow in the plaintext queue or underflow in the ciphertext queue.…”
Section: Plaintext Queue In Encryptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, although SCFB mode is modified from the conventional mode of cipher feedback (CFB) , it is shown in to be much more efficient to apply than CFB, resulting in much higher throughputs for a hardware‐based implementation of a block cipher such as the Advanced Encryption Standard (AES) . In fact, it can be shown that SCFB mode and the derived mode of pipelined SCFB (PSCFB) can approach efficiencies of 100%. In contrast, conventional CFB mode, when implemented to recover from any size of data loss in the channel, has an efficiency of less than 1% when used with AES.…”
Section: Introductionmentioning
confidence: 99%